Assessment of the Central Effects of Natural Uranium via Behavioural Performances and the Cerebrospinal Fluid Metabolome - P. Lestaevel; S. Grison; G. Favé; C. Elie; B. Dhieux; J. C. Martin; K. Tack; M. Souidi (Neural Plasticity)
Natural uranium (NU), a component of the earth’s crust, is not only a heavy metal but also an alpha particle emitter, with chemical and radiological toxicity. Populations may therefore be chronically exposed to NU through drinking water and food. Since the central nervous system is known to be sensitive to pollutants during its development, we assessed the effects on the behaviour and the cerebrospinal fluid (CSF) metabolome of rats exposed for 9 months from birth to NU via lactation and drinking water (1.5, 10, or 40 mg·L−1 for male rats and 40 mg·L−1 for female rats). Medium-term memory decreased in comparison to controls in male rats exposed to 1.5, 10, or 40 mg·L−1 NU. In male rats, spatial working memory and anxiety- and depressive-like behaviour were only altered by exposure to 40 mg·L−1 NU and any significant effect was observed on locomotor activity. In female rats exposed to NU, only locomotor activity was significantly increased in comparison with controls. LC-MS metabolomics of CSF discriminated the fingerprints of the male and/or female NU-exposed and control groups. This study suggests that exposure to environmental doses of NU from development to adulthood can have an impact on rat brain function.